In vitro evaluation of fungicides and bio-control agents against sunflower collar rot (Sclerotium rolfsii): IN VITRO EVALUATION OF FUNGICIDES AND BIO-CONTROL AGENTS AGAINST SUNFLOWER COLLAR ROT - NITESH DATT,; ANIL KUMAR,; A S RATHI, (Journal of Oilseeds Research, 2014)
The efficacy of different fungicides against Sclerotium rolfsii was tested using poison food technique under in vitro conditions and through seed treatment in screen house. Efficacy of fungicides in vitro against S. rolfsii showed that carboxin, vitavax power and hexaconazole completely inhibited mycelial growth up to 100 per cent at 100 ppm concentration. Thiram inhibited 95.8 per cent and propiconazole inhibited 98.1 per cent at 1000 ppm. Captan inhibited 80.6 per cent at 1000 ppm while, carbendazim only inhibited 18.5 per cent at 1000 ppm. Pencycuron have failed to show antifungal activity against S. rolfsii even at 1000 ppm. Evaluation of bio-agents against S. rolfsii in vitro revealed that Trichoderma harzianum showed maximum antifungal activity with 70.1 per cent inhibition of mycelial growth followed by T. viride (63.1%) and Bacillus spp. (53.7%). Seed treatment with fungicides and soil treatment with bio-agents significantly reduced the disease incidence of collar rot. Maximum collar rot control was found by carboxin (73.9%) followed by vitavax power (69.9%) and thiram (69.4%) by seed treatment under screen house conditions. For the bio-agents, T. harzianum showed maximum control of the disease (40.8%) followed by Bacillus spp. (36.9%) and T. viride (34.6%) in comparison to control.